Wróg dla syna, matka dla wnuka – caryca Katarzyna II i jej relacje z synem i wnukiem - Strzelczyk, Agata (Studia Edukacyjne, 2018)
This article is about Russian Empress Catherine the Great, her relations with her son Paul and grandson Alexander and role that she played in their upbringings. When Paul, Catherine’s only legal son was born, he was taken from her by Empress Elizabeth. That – and the fact, that Paul blamed Catherine for the death of his father – resulted in the fact, that they never develops proper, familial relation. On the other hand, Catherine was very active and affectionate grandmother, primarily for her oldest grandson, Alexander. She wanted to raise him to become ideal enlightened monarch. She took care of his education and even wrote fairy tales for him herself. Paul hated mother with bitter passion. Alexander loved her, but her influence shaped also his negative features. Catherine had undoubtedly great impact on both her son’s and grandson’s lives, but in the first case – impact was definitely negative and in second case – only arguably positive.